STUDY OF P-SELECTIN LEVELS AND HEMOSTASIS GENES GENETIC POLYMORPHISMS AMONG PATIENTS WITH GOUT - Akramova N.T., Nabiyeva D.A., Bobomurodov T.A., Bobomurodova D.T., (Central Asian Journal of Medicine, 2025)
Gout is a metabolic and inflammatory disorder characterized by hyperuricemia and crystal-induced arthritis, often accompanied by an elevated risk of cardiovascular events and thrombosis. P-selectin, a marker of platelet activation and endothelial dysfunction, has been implicated in thrombotic processes. Genetic polymorphisms in hemostasis-related genes may contribute to both hyperuricemia-related inflammation and thrombogenic potential. The objective of this study was to investigate P-selectin levels and common genetic polymorphisms in MTHFR, F5, F2, and PAI-1 genes among 80 patients with gout and 20 healthy controls to assess their combined role in increasing thrombotic risk. Plasma P-selectin levels and genotypic variations in MTHFR C677T, F5 G1691A, F2 G20210A, and PAI-1 675 4G/5G were analyzed in a cohort of gout patients (n = 80) and healthy controls (n = 20). Enzyme-linked immunosorbent assay (ELISA) was used to quantify P-selectin. Genotyping was conducted using TaqMan PCR. Statistical correlation analyses were performed to determine the relationship between elevated P-selectin levels and the presence of high-risk genotypes. Gout patients exhibited significantly elevated P-selectin levels (range: 0.01–3.58 ng/mL), with many exceeding the normal threshold (0.30 ng/mL), compared to controls (0.02–0.18 ng/mL). High-risk genotypes were notably more frequent among gout patients: MTHFR TT (13%), F5 AA (5%), F2 AA (22%), and PAI-1 4G/4G (62%). Correlation analysis showed a moderate positive relationship between P-selectin levels and genetic polymorphisms (r = 0.378, p = 0.00036), with R² = 0.143. Elevated P-selectin levels in gout patients are moderately associated with thrombosis-related genetic polymorphisms, suggesting an interplay between genetic predisposition and thrombo-inflammatory processes in gout.